COVID-19 IN PREGNANCY - Nursilri meidania; Dea Selvia; Rodiani - (Jurnal Kesehatan Saintika Meditory, 2022)
Coronavirus Disease 2019 (COVID-19) is a new disease that has never been identified in humans before. The type of virus is a single-strain RNA with a particle size of 120-160 nm. The coronavirus that caused a pandemic was first reported in Wuhan, China on December 31, 2019, is a new type of SARS-CoV 2 and has a genome sequence similar to SARS-CoV and MERS-CoV. This virus is dangerous and has caused deaths recorded as many as 532,340 in the world and 3,241 deaths in Indonesia on July 6, 2020. Pregnant women are included in the group that is vulnerable to infection. COVID-19 infection can cause various symptoms ranging from mild, moderate and severe. The main clinical symptoms that can appear are fever (temperature> 38 ° C), cough and difficulty breathing. These complaints can be accompanied by the presence of severe tightness, fatigue, myalgia, gastrointestinal symptoms such as diarrhea and other respiratory symptoms. The principles that must be considered in managing COVID 19 in pregnancy are early separation, aggressive infection control methods, testing for COVID 19 and other common infection tests, oxygen therapy if necessary, monitoring of fluid therapy,monitoring of the fetus and uterine contractions, mechanical ventilation associated with progressive respiratory symptoms, delivery planning and a team-based approach with multidisciplinary consultation